Mobile therapy: use of text-messaging in the treatment of bulimia nervosa - Shapiro, Jennifer R.; Bauer, Stephanie; Andrews, Ellen; Pisetsky, Emily; Bulik-Sullivan, Brendan; Hamer, Robert M.; Bulik, Cynthia M. (The international journal of eating disorders, 2010)
Objective To examine a text-messaging program for self-monitoring symptoms of bulimia nervosa (BN) within the context of cognitive-behavioral therapy (CBT). Method Thirty-one women participated in 12 weekly group CBT sessions and a 12 week follow-up. Participants submitted a text message nightly indicating the number of binge eating and purging episodes and rating their urges to binge and purge. Automatic feedback messages were tailored to their self-reported symptoms. Results Fully 87% of participants adhered to self-monitoring and reported good acceptability. The number of binge eating and purging episodes as well as symptoms of depression (BDI), eating disorder (EDI), and night eating (NES) decreased significantly from baseline to both post-treatment and follow-up. Discussion Given the frequent use of mobile phones and text-messaging globally, this proof-of-principle study suggests their use may enhance self-monitoring and treatment for BN leading to improved attendance, adherence, engagement in treatment, and remission from the disorder. © 2009 by Wiley Periodicals, Inc. Int J Eat Disord 2010; 43:513-519